Evaluating underlying inflation measures for Russia - Elena Deryugina; Alexey Ponomarenko; Andrey Sinyakov; Constantine Sorokin (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​We apply several tests to the underlying inflation metrics used in practice by central banks and/or proposed in the scientific literature, in an attempt to find the best-performing indicators. We find that although there is no single best measure of underlying inflation, indicators calculated on the basis of dynamic factor models are generally among the best performers. These best performers not only outdid the simpler traditional underlying indicators (trimmed and exclusion-based measures) but also proved to be economically meaningful and inter-pretable.
URN:NBN:fi:bof-201508201361
Keywords: E31; E32; E52; C32; 330